Khulu’ dalam perspektif kompilasi hukum Islam (KHI) - Safitri, Yayuk (Maliki Interdisciplinary Journal, 2024)
The resolution of domestic crises given by the wife and received by the husband is called khulu in Islamic law. This research examines the legal protection of women if the surrender of the khulu’ is determined and investigated. In addition, there is also a relationship between the provisions and the concept of khulu’ with the position of women in marriage law arising from the Compilation of Islamic Law related to Marriage Law. It was decided to use normative legal research methods in this study. with a legal approach. The results of this study indicate that the surrender of the khulu to the man to separate himself from the marriage bond is accompanied by the payment of ’iwadh’, namely the payment of money or goods to the man from the woman’s side in return, divorce. as. form of legal protection for women. The text says that ’iwadh is a system of legal protection provided by the state to women belonging to the khulu’.